2018
DOI: 10.1111/ijcp.13276
|View full text |Cite
|
Sign up to set email alerts
|

Group B streptococcus colonisation and associated risk factors among pregnant women: A hospital‐based study and implications for primary care

Abstract: Summary Background Group B streptococcus (GBS), which asymptomatically colonises the vaginal and rectal areas of women, is a leading cause of neonatal mortality and morbidity. This study aimed to determine the prevalence and factors associated with GBS colonisation among pregnant women in Shenzhen, China. Methods A hospital‐based cross‐sectional survey was conducted, using a multistage sampling method. Pregnant women at ≥28 weeks’ gestation completed a questionnaire and vaginal swabs were obtained for GBS anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
18
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 36 publications
3
18
1
Order By: Relevance
“…Studies conducted in Cameroon on GBS colonisation in pregnant women have focused on assessing the prevalence 12,13,15,16,19 but risk factors for GBS colonisation have not been systematically studied. For example, increasing epidemiological studies have demonstrated the relationship between obesity and GBS colonisation in pregnant women 1,23 . The impact of sociodemographics factors on GBS colonisation in pregnant women show the association with the level of income (p = 0006) with high prevalence (55.56%) found in patients with low income.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies conducted in Cameroon on GBS colonisation in pregnant women have focused on assessing the prevalence 12,13,15,16,19 but risk factors for GBS colonisation have not been systematically studied. For example, increasing epidemiological studies have demonstrated the relationship between obesity and GBS colonisation in pregnant women 1,23 . The impact of sociodemographics factors on GBS colonisation in pregnant women show the association with the level of income (p = 0006) with high prevalence (55.56%) found in patients with low income.…”
Section: Discussionmentioning
confidence: 99%
“…Group B streptococcus (GBS), also name as Streptococcus agalactiae, is a gram-positive bacterium know for its capacity to cause infection of the mother infection, fetus, neonatal sepsis and meningitis 1,2 . Early-onset diseases in infants such like pathogen causes chorioamnionitis 3 , preterm birth 4 , stillbirth 5 , meningitis 6 are the results of GBS vertical transmission from a colonised mother during or just before delivery.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in Spain between 2013 and 2015 found that performing genital hygiene twice or more daily was associated with a higher risk of GBS colonisation during pregnancy . In the study by Chen et al, a history of induced abortions, but not of spontaneous abortions, was associated with significantly lower GBS colonisation rates …”
mentioning
confidence: 97%
“…A better understanding of these risk factors and improved clinical management are ideally positioned to develop targeted efforts to reduce maternal and fetal morbidity and mortality. In the current issue of the IJCP , Chen et al had reported a hospital‐based cross‐sectional survey on pregnant women who were undergoing routine prenatal testing. Obstetric data and bacteriological cultures were available for 2121 participants.…”
mentioning
confidence: 99%
See 1 more Smart Citation